Enhancing graduate competitiveness: The role of the MBKM policy in Indonesian higher education - Wiryawan, Ryzki; Permana, Johar; Suryana, Asep; Suryadi, Suryadi (Indonesian Research Journal in Education |IRJE|, 2025)
This study examines the influence of the Merdeka Belajar Kampus Merdeka (MBKM) policy implementation on graduate competitiveness in Indonesian higher education, using Actor–Network Theory (ANT) as the mediating analytical lens. A quantitative research design using Structural Equation Modeling (SEM-AMOS) was applied to responses from 250 graduates across various universities and fields of study, including MBKM participants and non-participants. The findings indicate that the effective implementation of the MBKM policy significantly enhances graduate competitiveness, both directly and indirectly, as influenced by actor-network dynamics involving universities, industry partners, and technical systems. Key elements, including communication, resource support, and collaborative engagement, are demonstrated to drive improvements in employability and labor-market readiness. The study advances higher education policy discourse by empirically demonstrating that policy success depends not only on structural design but also on the capacity of stakeholder networks to translate policy into meaningful graduate outcomes.